Domain Fungsi Kognitif setelah Terapi Stimulasi Kognitif - Renata Komalasari (Jurnal Keperawatan Indonesia, 2014)
Terapi Stimulasi Kelompok (TSK) merupakan terapi kelompok yang terbukti efektif meningkatkan fungsi kognitif lanjut usia dengan demensia ringan-sedang. Penelitian ini bertujuan membuktikan efektifitas TSK dengan 14 sesiterhadappeningkatan fungsi kognitif di Kelurahan Binong, Tangerang, Indonesia. Sebanyak 43 orang mengikuti skrining demensia dengan Mental State Examination (MMSE) rentang. Jumlah responden yang mengukti pretes 24 orang. Attrition rate responden mencapai 79,1%. Hanya lima respondenmengikuti TSK hingga pos-tes.Kendati ada kenaikan skor MMSE 2,4 poin antara pre- dan pos-test, namun berdasarkan paired t test, tidak ada perbedaan signifikan antara skor MMSE pre- dan pos-tes secara keseluruhan (p=0,080; Î±=0,05)dan tidak ada perbedaanpre- dan pos-tes untuk tiap domain fungsi kognitif. Kecilnya jumlah sampel dapat memengaruhi hasil penelitian ini. Penelitian lebih lanjut dengan ukuran sampel lebih besar dibutuhkan guna memvalidasi temuan penelitian ini.AbstractCognitive Function Domain after Cognitive Stimulation Therapy (CST). CST is a group therapy proved effective at improving cognitive function of the elderly with mild to moderate dementia. The literature hinted no research reports on effectiveness of Cognitive Stimulation Therapy in the Indonesian community. This study aimed to prove effectiveness of CST in the Indonesian community and find which cognitive function domain improved after participating in 14 CST sessions. Purposive sampling was used with inclusion criteria: elderly of 45 and plus, living in Binong, Tangerang, havingmild to moderate dementia (Mental State Examination (MMSE) scores of 10-26, ability to communicate and understand Indonesian language.Attrition rate of respondents was 79,1%. Only 5 respondentsattended CST upto post-test. While 2,4 point increase was found on MMSE scores between pre- and post-test, paired t testshowed no significant difference between the two (p=0,080; Î±=0,05) and no differences found for each cognitive function domain. Future study is warranted with larger sample size to validate findings of this study.Â Keywords: cognitive function, cognitive stimulation therapy, elderly, Mini Mental State ExaminationÂ